The Possibilities of Improving the Human-Machine Co-Operation in Semi-Automatic Production Process - Dagmara Łapczyńska (Technologia i Automatyzacja Montażu)
Nowadays, modern production processes are undergoing intensive technological development, according to Industry 4.0 and Industry 5.0 assumptions. Despite the separate differentiation and numbering of these terms, the assumptions of the two approaches do not contradict each other. Industry 5.0 is a type of an extension of the drive for the highest possible degree of integration of automated systems (along with the pillars assumed in Industry 4.0) by finding a place where humans prove to be irreplaceable and their needs are identified as the most essential, central aspect. This leads to the implementation of semi-automated processes in which the cooperation between human and machine is the key. The paper presents an analysis and the results of the studies performed in company that produces vehicle control systems in automotive. The research includes quarter-a-year of studies and observation of production process. The studies aimed identifying waste in production process and proposing improvement methods, with particular reference to automated operations. Implementation of proposed improvements was mainly based on re-programming automated systems, but also on adding new process of cleaning brakes, that allowed to reduce the number of scrapped parts. Moreover, the implicated solutions allowed to achieve reduction of production process cycle time, financial savings and risk of the defects.